Microbiota e teores de aminas bioativas na carne maturada de bovinos de corte, com e sem estimulação elétrica da carcaça. - Filgueras, Renata Schmidt (2007)
Samples of contra-filet (muscle Longissimus Dorsi) of 12 carcasses of Red Angus bovines and zebuines mixed breeds, knocked down with approximately 350 kg and 3 years of age, treated with or without electric stimulation of low voltage in the period post-mortem were vacuum-packed and stored under refrigeration ( 1,0±0,5ºC) for until 56 days. After 0, 7, 14, 35 and 56 days of maturation were made the determination of bioactive amines (putrescine, cadaverine, histamine, tiramine, serotonin, agmatine, tryptamine, feniletilamine, espermine and espermidine), standard count in plaque of aerobes microorganisms and total count of lactic bacteria. The count of microorganisms of the samples has correlated positively during the storage time (r>0,91 e p<0,001), achieving maximum scores of 6,67 and 7,6 LogUFC.g-1 for viable microorganisms aerobes and lactic bacteria, respectively, after 56 days. The breed variation of the animals and the electric stimulation of the carcass have not demonstrated to cause significant effects in the microbiotics and tenor of bioactive amines during the period observed, except as for the tenors of espermine, after 14 days, when a bigger concentration of such polyamine was detected in the mixed breed meat. Significant positive correlations (p<0,001), were also observed between the lactic bacteria count and the total of bioactive amines in the meat of carcass electrically stimulated, in both Red Angus and zebuines mixed breeds, which it did not occur in the meat of carcass without post-mortem electric stimulation. .